Designing and Developing a Plastic Bottle Shredding Device with an RFID-Based Waste Management System at Jakarta Global University Campus - Arlince, Meishin; Jaenul, Ariep; Putri, Arisa Olivia (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This study investigates the measurement of plastic waste, commonly found in public areas such as the Global University of Jakarta campus, using both manual and automated weighing systems. This research aims to compare the accuracy of a manual scale and an automated load cell system, with a monetary conversion of 1 gram equating to IDR.3. This research employs a Research and Development (R&D) design where experimental tests were conducted to measure plastic waste weight with both systems. The first test revealed a weight range of 6.5–9.5 grams using the load cell, compared to 6.7–9.7 grams on the manual scale. The second test showed a range of 16.5–21.1 grams for both systems, while the third test showed 31.8–36.3 grams on the load cell and 32–36.8 grams on the manual scale. The error margin between the two systems remained below 3%, indicating a high level of accuracy in the automated system. The findings demonstrate that the automated system reliably approximates manual measurements, with each gram of plastic waste valued at IDR.3. To enhance the system's performance, future research should focus on incorporating a specialized cutting mechanism for plastic bottles to reduce vibrations, optimizing load cell placement for precision, and constructing the prototype from durable materials such as stainless steel to ensure both safety and measurement accuracy. These improvements could further advance the system’s efficacy in plastic waste management.